2022
DOI: 10.1108/rausp-02-2022-0063
|View full text |Cite
|
Sign up to set email alerts
|

Does gender diversity moderate the relationship between CSR committees and Sustainable Development Goals disclosure? Evidence from Latin American companies

Abstract: Purpose This study aims to investigate the association between the presence of a corporate social responsibility (CSR) committee and Sustainable Development Goals (SDGs) disclosure, as well as the moderating role of gender diversity in this relation. Design/methodology/approach The sample consists of 897 annual observations from 238 firms from Argentina, Brazil, Chile, Colombia, Mexico and Peru for 2018–2020. The data were collected from the Refinitiv database. The proposed model and hypotheses were tested u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 129 publications
0
12
0
Order By: Relevance
“…Based on the studies by Daniel-Vasconcelos et al (2022), Gallén and Peraita (2018), Naeem et al (2023), andWen et al (2023), we employ the Panel-Corrected Standard Error (PCSE) estimator as an alternative method. Since FGLS may overestimate the significance of the coefficients (Beck & Katz, 1995), the performance of PCSE may be better than the FGLS estimator in samples where the number of periods is equal to or greater than the number of cross sections (Hossain, 2016).…”
Section: Robustness Analysismentioning
confidence: 99%
“…Based on the studies by Daniel-Vasconcelos et al (2022), Gallén and Peraita (2018), Naeem et al (2023), andWen et al (2023), we employ the Panel-Corrected Standard Error (PCSE) estimator as an alternative method. Since FGLS may overestimate the significance of the coefficients (Beck & Katz, 1995), the performance of PCSE may be better than the FGLS estimator in samples where the number of periods is equal to or greater than the number of cross sections (Hossain, 2016).…”
Section: Robustness Analysismentioning
confidence: 99%
“…Related to the above, recent research has also studied SDGs compliance reporting in relation to sustainability performance disclosure, enabling a change of direction in the approach to strategic objectives and management with stakeholders that can meet their interests, enhancing legitimacy, as well as providing greater scope for disclosure of the environmental and social practices proposed by the SDGs. (Calabrese et al 2021;Cortés, 2022;Daniel-Vasconcelos et al, 2022;Rosati & Faria, 2019;Tsalis et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…promotion by governments, regulatory bodies, and professional associations(Reis et al, 2020;Pineda-Escobar, 2019). As pointed out in studies on the SDGs in Latin America such as those byCortés (2022) andDaniel-Vasconcelos et al (2022), the contribution of organizations to the SDGs is still under development and should be oriented towards the improvements of health services, community development, gender equality in employment opportunities and initiatives to combat poverty, climate change, care for biodiversity and anti-corruption measures.Institutional and legitimacy theories are the most recurrent in the literature review that explains that sustainability reporting in Latin America is due to a regulatory or normative influence and as a positive justification of activities with high environmental and social impact on society. However, stakeholder theory is only considered in the studies byClemente et al …”
mentioning
confidence: 99%
“…Rao & Tilt, 2021), while conventional banking has been found to have no correlation (Kusuma et al, 2018) and has not been found in Islamic banking. Other empirical evidence documents the correlation of board size and an independent board of commissioners on the financial performance of Islamic banks (Intia & Azizah, 2021;Umam & Ginanjar, 2020;Rahmawati, 2017), but the correlation of gender diversity has only been found in conventional banks (Daniel-Vasconcelos et al, 2022) and nonbanks (Brahma et al, 2021). So it is necessary to do research related to green banking disclosure in Islamic banks.…”
Section: Introductionmentioning
confidence: 99%